Community Perceptions Around Special Need Schools in Purwosari Village Against Children with Special Needs - Indra Prastianing Zahro; Helis Ira Setiawati; Rima Widya Wulandari; Qurroti A’yun; Imaniar Purbasari (Yayasan Insan Mulia Bima, 2023)
Children with special needs are social beings who cannot be separated from social interaction. Some people still underestimate children with special needs because of their limitations and deficiencies. Community perceptions cannot be separated from the interactions that children with special needs have with their surroundings. This study aims to determine the perceptions and interactions that occur between the community and children with special needs. In order to achieve these objectives, the researcher uses qualitative methods with a case study approach. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the community's perceptions around the Purwosari State Special School are well addressed by the positive response given by the community to children with special needs.